The Gnostic, Vol.1, No.02, August 1885 - Chainey, George; Kimball, Anna (My University, 1885)
The Gnostic (George Chainey and Anna Kimball) 1, no. 2 (August 1885). Individual Archives – Periodicals G-N. New Age Movements, Occultism and Spiritualism Research Library. Valdosta State University. https://hdl.handle.net/10428/5010 .
Keywords: Periodicals; Gnosticism; Occultism; Spiritualism; Theosophy; Chainey, George, 1851-1935